PENINGKATAN KUALITAS DAN PRODUKTIVITAS PANGAN TRADISIONAL ACEH IKAN KEUMAMAH BERSKALA INDUSTRI RUMAH TANGGA - Muhardina, Virna; Rahmiati, Tengku Mia (Universitas Djuanda Bogor, 2017)
THE IMPROVEMENT OF QUALITY AND PRODUCTIVITY OF ACEHNESE FOOD âKEUMAMAHâ IN HOME INDUSTRIAL SCALEABSTRACTKeumamah is a typical Acehnese food product made from tuna that has been through the boiling, smoking and drying stage (known as keumamah fish or wooden fish). This product is processed manually by home industry, thus causing limitations in the quantity and quality production. This devotional activity aims to offer solutions by giving slicer and spinner tools to home industries